Effects of Levilactobacillus brevis GKEX supplementation on exercise performance and fatigue resistance in mice - Lin, Tzu-Chun; Chen, Chin-Chu; Tsai, You-Shan; Lin, Shih-Wei; Huang, Chi-Chang; Hsu, Yi-Ju (Frontiers in Nutrition, 2025)
BackgroundExercise-induced muscle fatigue is a major challenge for athletes. Our previous study indicated that Levilactobacillus brevis GKEX improved endurance and reduced fatigue in mice. This study aimed to further evaluate the effects of different preparations of L. brevis GKEX on exercise performance and fatigue resistance.MethodsEight-week-old male ICR mice were divided into six groups (n = 8): vehicle, BCAA, low-dose GKEX (0.0615 mg/day), high-dose GKEX (0.615 mg/day), heat-killed GKEX (0.615 mg/day), and freeze-killed GKEX (0.615 mg/day). Treatments lasted for four consecutive weeks. Exercise performance, fatigue-related biochemical markers, and gut microbiota composition were assessed.ResultsCompared with BCAA, L. brevis GKEX significantly improved aerobic performance, including forelimb grip strength and running-exhaustion time. It enhanced lactate clearance and glycogen storage in the liver and muscles while reducing lactate production and blood urea nitrogen levels after exercise. L. brevis GKEX supplementation also increased key short-chain fatty-acid–producing bacteria in the intestines.ConclusionOral administration of different doses of live and dead L. brevis GKEX promoted exercise performance and ameliorated fatigue, especially live GKEX. These findings suggest that L. brevis GKEX may serve as an ergogenic aid for athletes and support broader applications across various product forms.